Newcastle and Northumberland - British Archaeological Association.
1 online resource
Keywords: This book is an outcome of the summer conference on the theme Newcastle and Northumberland. It examines the heritage of north-eastern England ranging from the sculpture of the Roman occupation through the monuments and architecture of the Anglo-Saxon and Norman periods.